Preferensi Konsumen Atas Atribut Aplikasi Mobile Banking Bank Syariah Indonesia Menggunakan Analisis Konjoin - Septiana Ulfah; Saladin Ghalib (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: The approach used in this research is to use quantitative research regarding the analysis of the influence of service quality, location, product quality and price on consumer repurchase interest at Depo Gemilang. Banjarmasin City With a population of all buyers or customers who buy building materials at the Gemilang Depot, Banjarmasin City. The research results show that service quality has a significant positive effect on consumer repurchase interest and product quality has a significant positive effect on consumer repurchase interest